Re-analysis of unassigned hepatitis C virus (HCV) strain CYHCV025: Evidence of a highly divergent lineage within genotype 1. - Oikonomopoulou, M; Demetriou, V L; Kostrikis, L G; Paraskevis, D (Mol Phylogenet Evol, 2017)
HCV global sequences have been classified into 7 genotypes, several subtypes and a number of unassigned sequences. Our aim was to perform an in depth investigation of the taxonomic relationships of the unclassified CYHCV025 strain by means of phylogenetic analysis. Phylogenetic tree reconstructions were performed using ML methods on full-length genomic and partial HCV alignments. Phylogenetic analysis of full-length sequences revealed that CYHCV025 clustered close to the root node of genotype 1, showing distant genetic relationships to all previously classified subtypes and unclassified sequences. Single section analysis using the SSE showed that the distances between the query and all subtypes were much higher than distances within and between subtypes of genotype 1 (p<0.05). Recombination analysis revealed no evidence for intersubtype or genetic mixing between the query and the references from different genotype 1 subtypes. Different analyses revealed that CYHCV025 is the most genetically divergent within genotype 1, showing no high- or low-level clustering with any of the previous subtypes or unclassified sequences. Identification of a single lineage within a genotype without any late branching can be explained by "genetic isolation" until the late stage of HCV epidemic spread.
Keywords: DNA, Viral; Genome, Viral; Genotype; Hepacivirus; Humans; Phylogeny; Recombination, Genetic; RNA, Viral; Sequence Analysis, DNA